Assessment of Micro-vessel Density in Brain Glioma by CD105 Expression - Hiva Saffar; Marzieh Mirzaii; Elham Mirzaian2050@gmail.com; Farid Kosari (Iranian Society of Pathology, 2018)
Background& Objective: Micro-vascular proliferation is an important histological feature of brain glioma with more vascular proliferation is present in higher grades of glioma. CD 105 is expressed in new actively proliferating and immature endothelial cells in tumor environment  and appears to be capable to distinguish between malignant neo-vasculature and normal vessels. Methods: This study was designed to evaluate the Micro-Vessel Density(MVD) in different grades of brain glioma based on CD 105 expression by Immunohistochemistry method to determine whether it can be a helpful marker for rumor grading or not. Paraffin blocks of formalin fixed samples of brain astrocytic glioma were retrieved and IHC was performed using anti-CD105 monoclonal mouse antibody. Results: Total number of 48cases of  low and high grade astrocytic gliomas were evaluated.We noted that there was a positive correlation between MVD evaluated by CD105 and tumor grade, meaning that expression was significantly greater in tumors with higher grade (P=0.019). Conclusion: We concluded that MVD quantified by CD 105 has positive correlation with tumor grade. Also we think that expression of CD 105 specially in low-grade glioma can serve as a basis for selective treatment option in combination with current standard care .